2009
DOI: 10.1111/j.1533-2500.2009.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Is Chronic Pain Associated With Somatization/Hypochondriasis? An Evidence‐Based Structured Review

Abstract: Somatization is commonly associated with chronic pain and may relate to pain levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 109 publications
(131 reference statements)
4
33
1
Order By: Relevance
“…The number of patients with HSCL-25 scores above the clinical cutoff of 1.75 was about twice that of the Norwegian normal population. Our findings are in line with a well-known association between emotional distress and chronic pain [33][34][35][36]. Neurobiological research suggests that pain and emotional distress are driven by overlapping pathophysiological processes in the brain and body [37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…The number of patients with HSCL-25 scores above the clinical cutoff of 1.75 was about twice that of the Norwegian normal population. Our findings are in line with a well-known association between emotional distress and chronic pain [33][34][35][36]. Neurobiological research suggests that pain and emotional distress are driven by overlapping pathophysiological processes in the brain and body [37][38][39].…”
Section: Discussionsupporting
confidence: 93%
“…33 Somatization does not represent a diagnostic category but attends by an increased probability for somatoform pain disorders. The role of somatization processes regarding pain generalization is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…One study found hypochondriasis in 50% of patients in a pain clinic [22], and another found high health anxiety predictive of abdominal pain a year later [23]. Still another found hypochondriasis associated with chronic pain and pain intensity [24]. Of course, these associations do not establish cause; painful symptoms may lead to anxiety about health.…”
Section: Discussionmentioning
confidence: 98%